Healthy snacks in hospitals: Testing the potential effects of changes in availability. Issue 3 (October 2021) - Allan, Julia L; Duthie, Shannon; Heddle, Maureen; McKenzie, Fiona; Webb, Susan; Johnston, Marie
Background: Hospitals offer snacks for sale to patients, staff and visitors. Aim: As food choice is heavily influenced by the options available, the present study (a) audited snack availability and purchase in NHS hospital sites across a large UK city; and (b) tested the potential effects of changes to this availability in an online choice experiment. Methods: In Study 1 (audit), single-serve snacks ( n =376) available in 76 hospital food retail units were audited. Purchasing data were obtained from six food retail units over four weeks (27, 989 sales). In Study 2 (online experiment), participants ( n =159) chose snacks from pictured ranges containing 25% (minority), 50% (equivalent) or 75% (majority) healthy options. Results: Available single-serve snacks varied markedly in calorie (18–641 kcals), fat (0–39 g), sugar (0.1–76 g) and salt (0–2.9 g). Only 30% of available snacks were healthy options and only 25% of the most commonly purchased snacks were healthy options. In Study 2, snack choice was significantly associated with the availability of healthy options in the choice array (X 2 (2) = 59.71, p<.01). More participants made healthy choices when product ranges contained 75% healthy options compared to 50% (p<.01) and 50% healthy options compared with 25% (p<.01). Conclusions: Healthy snacks are readily available in NHS sites but there is a greater relative variety of unhealthy snack products. Many consumers continue to purchase unhealthy items. Further increasing the availability and variety of healthy options may support consumers to make healthier choices.